Territorial Brand Development and Evaluation (The Case of Ekaterinburg) - Nаtаliа V. GONCHAROVA; Liudmila V. DAINEKO (Communications of International Proceedings, 2020)
The article discusses branding of a territory (city or region) as a tool to enhance its competitiveness and stimulate its socio-economic development. We focus on the case of Ekaterinburg (Russia), describe the competitive advantages of this city, and show the need for building a stronger city brand. We also compare the position of Ekaterinburg in various national city rankings. The conclusion is made that rankings that use formalized (objective) indicators are quite effective in the evaluation of a city brand's performance and territorial branding in general.
Keywords: Branding; Brand of a Territory; Region's Brand Image; City Brand.